A los habitantes de las Indias - Lardizábal y Uribe, Miguel de, 1744-1824 ([publisher not identified], 1815)
According to Medina (cited above), this circular was subscribed to in Madrid on July 20, 1814 and authorized in Mexico on February 2, 1815. The author invites his compatriots in the New World to remain loyal to Ferdinand VII.